(untitled) (Халықаралық қатынастар және халықаралық құқық сериясы, 2023)
As Kazakhstan and China celebrated thirty years of establishment of bilateral relations recently, a brief analysis of the bilateral state-to-state relations indicates to the overall stability and forward momentum. Several significant developments were witnessed both in China and in Kazakhstan and in the bilateral relations, specifically in their respective material capability build-up, exertion at the regional levels, expanding economic ties and strengthening institutional contacts, but also to the rising popular discontent on several issues. This article recounts first the major developments in these two countries and how the bilateral state-to-state relations flowered in different areas of diplomacy, economy and energy fields. Nevertheless, several problems also beset the bilateral relations, including regional balancing efforts, rising nationalism, Uighur issue, cross-border river sharing, rising debt and others, the resolution of all of which could determine future trajectory of these ties. It is argued here that following its “multi-vector” policies, Kazakhstan has been balancing both the traditional player Russia and a rising China to see that no single power is able to dominate the regional security situation. Key words: Kazakhstan, China, bilateral Relations, Belt and Road Initiative, economic Relations